Arsenic Removal by Adsorptive Flotation Methods - Yenial, Ünzile; Bulut, Gülay; Ali Sirkeci, Ayhan (Wiley, 2014)
Arsenic being one of the major pollutants was removed from dilute aqueous solution by Adsorbing colloid flotation (ACF) and adsorption onto natural goethite. Flotation was subsequently applied as an effective solid/liquid separation method. The ACF tests showed that acidic aqueous medium (pH 5.5) favored the removal of As(V). Natural goethite was also found to be a good adsorbent for arsenic removal at pH 3. The optimum conditions were tested on process water and it was found that the residual arsenic content was lowered below 0.1 ppm with ACF and 0.2 ppm with adsorptive flotation.